The multitasking of household production - Charlene Marie Kalenkoski; Gigi Foster (Institute for the Study of Labor (IZA), 2010)
The standard household production model does not incorporate multitasking, although time-diary data reveal that individuals regularly multitask. We formulate a model where time spent in child care can be sole-tasked or multitasked with other household production activities. This model implies associations between household productivity factors and both child outcomes and parental time use. We then use data from the Longitudinal Study of Australian Children and the Australian Time Use Surveys to examine the empirical validity of these implications. Consistent with our model's predictions, household productivity factors are associated both with child outcomes and parental time use.
Keywords: D13; J13; 330; Multitasking; child care; household production; Haushaltsproduktion; Produktivität; Eltern; Zeitallokation; Kinderbetreuung; Zeitbudgetforschung; Australien